2016
DOI: 10.1007/s40750-016-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Adversity, Adaptive Calibration, and Health: The Case of Disadvantaged Families

Abstract: Epidemiologists and medical researchers often employ an allostatic load model that focuses on environmental and lifestyle factors, together with biological vulnerabilities, to explain the deterioration of human physiological systems and chronic degenerative disease. Although this perspective has informed medicine and public health, it is agnostic toward the functional significance of pathophysiology and health deterioration. Drawing on Life History (LH) theory, the current paper reviews the literature on disad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 133 publications
2
29
0
6
Order By: Relevance
“…More generally, it is therefore possible that our results reflect the existence of coadapted life history strategies, where traits that promote future orientation and organismal longevity cluster together in meaningful functional composites (Figueredo et al, ; Figueredo, Vasquez, Brumbach, & Schneider, ; Luoto, Krams, & Rantala, ; Minkov & Bond, ; Sherlock & Zietsch, ). The link between family income and height suggests one such composite, indicating the existence of slower life history strategies in families with higher income (cf., Cabeza de Baca, Wahl, Barnett, Figueredo, & Ellis, ; Griskevicius, Tybur, Delton, & Robertson, ; Lynch, ; Woodley of Menie et al, ). Our results are generally consistent with the hypothesis that internal factors (here: less robust immunity system) that increase susceptibility to infectious disease affect differences in life history strategies at the phenotypic (Murray, Gildersleeve, Fales, & Haselton, ) and genotypic levels (Figueredo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, it is therefore possible that our results reflect the existence of coadapted life history strategies, where traits that promote future orientation and organismal longevity cluster together in meaningful functional composites (Figueredo et al, ; Figueredo, Vasquez, Brumbach, & Schneider, ; Luoto, Krams, & Rantala, ; Minkov & Bond, ; Sherlock & Zietsch, ). The link between family income and height suggests one such composite, indicating the existence of slower life history strategies in families with higher income (cf., Cabeza de Baca, Wahl, Barnett, Figueredo, & Ellis, ; Griskevicius, Tybur, Delton, & Robertson, ; Lynch, ; Woodley of Menie et al, ). Our results are generally consistent with the hypothesis that internal factors (here: less robust immunity system) that increase susceptibility to infectious disease affect differences in life history strategies at the phenotypic (Murray, Gildersleeve, Fales, & Haselton, ) and genotypic levels (Figueredo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that all LH traits vary on a slow-fast continuum (Del Giudice et al, 2015 ). More particular fast and slow LH strategies can be considered as coordinated and integrated patterns of metabolic, cognitive, behavioral, and personality traits (for details see Brumbach et al, 2009 ; Ellis et al, 2009 ; Figueredo et al, 2013 ; Del Giudice et al, 2015 ; de Baca et al, 2016 ). Slow LH strategies can be characterized by future oriented attitudes, a relatively long-term focus in behavioral strategies; for example, an ability to delay gratification.…”
Section: The Slow-fast Continuummentioning
confidence: 99%
“…which represent greater environmental harshness. Correspondingly, low SES was found to be associated with traits linked to fast LH strategies, such as impulsivity, risk-taking, and unrestricted sociosexual orientation (Brumbach et al, 2009 ; Belsky et al, 2010 ; Nettle, 2010 ; Griskevicius et al, 2011 ; de Baca et al, 2016 .). However, according to more recent findings, it is controversial to apply SES to represent harshness: some research has shown low SES as an indicator of resource scarcity whereas other studies have supported SES as a cue for mortality-morbidity threats (see Griskevicius et al, 2011 ; Belsky et al, 2012 ; Chang and Lu, 2018 for more details).…”
Section: Negative Early-life Experiences and Fast Life History Stratementioning
confidence: 99%
“…Stress response systems further coordinate across other physiological systems ( e.g. , the gonadal axis) to regulate sexual maturation and reproduction [9 •• ,19,2527]. …”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 99%